Doktrin Bi-La-Kaifa Menurut Al-Asy’ari - Ibrahim, Lutpi (Jurnal Usuluddin, 1995)
The author studies the controversial doctrine of bi-la-kaifa according to Imam Ashari as well as other scholars, such as Ahmad Ibn Hambali.